Association between Chronological Age and IGF-1, IGFBP-3, and CTX Levels in Saliva of Children through Younger Adult Population with Varying Periodontal Status - Abdullah Almalki; Julie Toby Thomas; Saud Alotaibi; Mansour Alasiri; Hamdan Alamri; Mohamed Helmy Salama (MDPI AG, 2022)
The quest for the most precise and non-invasive technology to monitor the pubertal growth spurt is driven by the role of growth determination in orthodontics. The objective of this study was to estimate the levels of salivary insulin-like growth factor-1 (IGF-1), IGF-binding protein-3 (IGFBP-3), and cross-linked C-terminal telopeptide of type I collagen (CTX1), and to analyze whether the levels of these biomarkers vary among different chronological age groups with and without periodontal disease. Eighty participants were divided into three groups based on their chronological age: group 1: 6-12 years; group 2: 13-19 years; and group 3: 20-30 years. The assessed clinical parameters included the simplified oral hygiene index (OHI-S), bleeding on probing (BOP), probing pocket depth (PPD), clinical attachment loss (CAL), and community periodontal index (CPI). Using ELISA kits, the IGF-1, IGFBP-3, and CTX1 levels in the saliva samples were estimated. The salivary concentration of IGFBP-3 was significantly associated with age and gender (p < 0.01). However, no significance was observed between subjects with and without periodontal disease. Significant associations existed between the values of IGF-1, IGFBP-3, and CTX1 in saliva among subjects from the various chronological age groups. Estimation of salivary IGF-1 and IGFBP-3 could serve as a useful tool in the assessment of growth maturity and bone remodeling patterns during orthodontic treatment planning.